Pinkfeet in Europe - The effect of cold weather of February 1956 on the distribution of Pink-footed Geese in north-west Europe - Holgersen, Holger (Wildfowl, 1957)
In the latter half of January 1954 severe winter weather–with frost and snowstorms–burst in over a wide area reaching from West England and eastwards, including at least Northern Germany and Denmark. As a direct consequence, a great many Scandinavian migrants, having arrived in the autumn in the British Isles, either starved or froze to death (instinct birds), or were forced to undertake a second emigration within a few months (weather birds), an exodus which brought large numbers of birds far southwards and out of reach of the threatening weather. This was clearly demonstrated, not only by direct field observations in Western France, in Spain and Portugal, but also by numerous recoveries of ringed birds in most of Western Europe, from England to Gibraltar. The birds involved included many Norwegian Lapwing, Fieldfare, Redwing, Common Gull, Black-headed Gull and others (Holgersen 1954). A parallel situation was created when in February 1956 another sudden and unusually severe spell of winter weather covered the northern parts of Central Europe. Denmark, Northern Germany and Holland were greatly affected. As expected this weather situation soon gave a good many recoveries of ringed birds, individuals found starving or frozen to death. But other recoveries were made in places and at times which clearly showed that the birds had been trying to escape and–with or without success–find areas with more favourable conditions.